Barra do Garças-MT, perspectives from the Connected Smart Cities Ranking - Ravache, Rosana Lia; Paula , Diana Carolina Jesus de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Objective - analyze the indicators of a smart city for the municipality of Barra do Garças - MT, due to its recognized importance in the Araguaia Valley. Methodology - adoption of the Connected Smart Cities Ranking (RCSC), developed by Urban Systems to identify Brazilian cities with the greatest growth potential from 50 thousand inhabitants. Originality/relevance - The choice by RCSC occurred because it addresses ISO 37122: Sustainable cities and communities and, consequently, the Brazilian version, which is NBR 37122 Sustainable cities and communities. Results - Despite being outside the top 100 in 2022 and 2023, it scored well on specific indicators, similar to those of the best-ranked small cities. By focusing on these indicators, public management can adopt strategies to improve performance and make the city smarter and more sustainable. Theoretical/methodological contributions – the RCSC made it possible, based on the thematic axes and their indicators, to observe how the municipality managed the city’s management between the years of study. Social and environmental contributions – It made it possible to identify the thematic axes with the best results, being urbanism, health and education, due to the indicators that evolved during the period analyzed.